Human engineering at Microsign - Varkkey, Biju (London : Indian Institute of Management, Ahmedabad, 2024)
Microsign is a small manufacturing unit located in Gujarat. Despite of the fact that half of the workforce is physically impaired, the dedication of the top management team and the unique value system has steered the organization towards success. Microsign has developed a unique work culture where both physically able and disable persons are treated equally and fairly. As the firm grows, different challenges are cropping up regarding the HR policies and practices. The case discusses some emerging HR issues like diversity management/reasonable accommodation, importance of formal HR policies and human resource management in a growing organization.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Personnel management -- Case studies; Business -- Growth -- Case studies